Biologia e nicho de espermatogônias tronco em catetos (tayassu tajacu) adultos - Paulo Henrique de Almeida Campos Junior (2011)
In the seminiferous epithelium, spermatogonial stem cells (SSCs) are located in a particular environment called niche that is controlled by the basement membrane, key testis somatic cells, and by factors emanating from the vascular network. However, the role of Leydig cells (LC) as a niche component is not yet clearly elucidated. Recent studies showed that peccaries (Tayassu tajacu) present a peculiar LC cytoarchitecture,where these cells are located around the seminiferous tubules lobes, making the peccary an unique model for investigating SSCs. This peculiarity allowed us to subdivide the seminiferous tubules cross-sections in three different regions [tubuletubule (T-T); tubule-interstitium (T-I); and tubule-LC contact (T-LC)]. Our aims were tocharacterize the different spermatogonial cell types in this species and to determine the location and/or distribution of the SSCs along the seminiferous tubules. Compared to differentiating spermatogonia (Adiff), undifferentiated spermatogonia (Aund) presented a noticeably higher nuclear volume (p<0.05), allowing an accurate evaluation of their distribution. Immunostaining analysis demonstrated that all Aund (As,Apr and Aal) were GFRA1+. However, only A-single (As) and A-paired (Apr) spermatogonia were located in the T-I (p<0.05), whereas clones containing eight or more undifferentiated cells (Aal) were situated close to the T-LC (p<0.05). The expression of CSF-1 was observed in LC and peritubular myoid cells (PMC) while its receptor was present in LC and in GFRA1+ Aund. Taken together, our findings strongly suggest that, different from PMC, LC play a negative role in the SSC niche and physiology and that these steroidogenic cells are probably involved in the differentiation of Aund toward type A1 spermatogonia.